The Uruguay Round Agreement on Agriculture: Will It Immiserize the Filipino Farmer? - Clarete, Ramon L. (Kasarinlan: Philippine Journal of Third World Studies; Vol 24 No 1-2 (2009): The Philippines in the WTO, 2011)
The paper argues that requiring General Agreement on Tariff and Trade (GATT) member–countries to remove agricultural quantitative import restrictions is not as disadvantageous to Filipino farmers as critics of the Uruguay Round Agreement on Agriculture suggest. It refutes claims to the contrary, showing how the agricultural provisions of the new GATT treaty will benefit Filipino farmers, and arguing that these provisions seek to shift market shares in agricultural trade towards small countries like the Philippines. It points out, for example, that the much-maligned ban on government agricultural subsidies is actually favorable to countries that cannot afford to provide such subsidies to its farmers, such as the Philippines. It claims that the lowering of tariff barriers on agricultural products in the developed world will open hitherto inaccessible markets to developing countries that heavily export agricultural produce. For the Philippines, these new market access opportunities will translate to a large increase in profits from agricultural exports, if the country retains its current share in the world market. The paper allays fears that developed countries will gain significantly from the treaty while the inverse will happen to developing countries by discussing the treaty’s measures against unfair trade and import surges. For this purpose, it also makes mention of the measures in the treaty designed to enhance the global competitiveness of its signatory countries. The paper concludes by saying that a rejection of the treaty entails a rejection of the aforesaid benefits, which would imperil Philippine agricultural production. A decline in income from agricultural exports because of the country’s withdrawal from world trade will lead to the impoverishment of Filipino farmers, and consequently of Filipinos throughout the country.
Keywords: GATT member countries · agricultural import restrictions · Uruguay Round Agreement · global competitiveness · Philippines